Construction of a Scale to Measure Correlates of Adoption of Sustainable Domains in On-Farm Testing Interventions - Safna Vatakke Kandy Meethal; Allan Thomas (Indian Journal of Extension Education, 2024)
The study was conducted in 2023 with an aim to identify SRDs and develop a reliable scale for adoption correlates within these domains. The development of the scale follows a systematic Likert scale development methodology involving identification of SRDs of OFT interventions, delineation of different dimensions of each correlate of adoption, dimension analysis and selection, and its standardisation by reliability and validity assessment. The final scale comprises 32 dimensions under seven adoption correlates, selected via exploratory factor analysis (EFA) and item discrimination index calculation. The scale demonstrated strong content, construct, and convergent validity, with an average variance extracted (AVE) value of 0.69 and composite reliability (CR) score of 0.97. It also exhibited high internal consistency, with a Cronbach’s alpha of 0.97 and a split-half reliability coefficient of 0.963. The standardized scale is effective for measuring factors related to the adoption of improved technologies and practices, providing a valuable tool for researchers in various fields. The administration of the developed scale and the subsequent correlation analysis revealed significant relationships, with human resource correlates showing the highest correlation (r = 0.895), followed closely by technological (r = 0.872) and economic correlates (r = 0.87), underscoring the critical factors influencing farmers’ adoption behaviour.